1992
DOI: 10.1063/1.860199
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic backward-wave oscillators: Theory and experiment

Abstract: Microwave sources based on backward-wave oscillators driven by relativistic electron beams are capable of producing high-power coherent radiation in cm and mm wavelength regime. Although there have been a number of experiments reported over the last decade on this topic, there are only a few publications providing a theoretical description of these devices. Thus, there is a need for theoretical models which can be compared in detail with the experimental data. This work is devoted to fill this need and applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…6(a)), at a sufficiently large shift of the Cherenkov synchronism point "C" from the dispersion curve extremum point "B," a transition from the p-mode operation regime to the traditional BWO regime must take place. According to the conventional BWO model, [18][19][20][21] in the latter regime the excited field can be presented as a combination of the fundamental volume modeĈ À and its evanescent synchronous spatial harmonic. Here we describe the procedure of transformation from the surface-wave oscillator model (12) to the conventional BWO model when synchronous waveĈ þ is converted into the spatial harmonic with a negligibly small energy flux.…”
Section: Appendix: Transition To the Canonical Model Of Relativistic Bwomentioning
confidence: 99%
See 2 more Smart Citations
“…6(a)), at a sufficiently large shift of the Cherenkov synchronism point "C" from the dispersion curve extremum point "B," a transition from the p-mode operation regime to the traditional BWO regime must take place. According to the conventional BWO model, [18][19][20][21] in the latter regime the excited field can be presented as a combination of the fundamental volume modeĈ À and its evanescent synchronous spatial harmonic. Here we describe the procedure of transformation from the surface-wave oscillator model (12) to the conventional BWO model when synchronous waveĈ þ is converted into the spatial harmonic with a negligibly small energy flux.…”
Section: Appendix: Transition To the Canonical Model Of Relativistic Bwomentioning
confidence: 99%
“…In the Appendix we consider the transition from the model of surface-wave oscillator operating in the p-mode regime to the canonical model of relativistic backward wave oscillator (BWO). [18][19][20][21] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors [1][2][3][4][5][6][7][8][9][10][11][12] have focused their attention on this device for more efficient operation at high-power levels, and important results have been obtained both experimentally and theoretically. In order to further enhance the output power of microwave and the conversion efficiency of electron beam to microwave radiation, some scientists [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] have introduced background plasmas into the BWOs, and both theoretical and experimental results have demonstrated that the background plasmas improve the beam-waveguide interaction dramatically.…”
Section: Introductionmentioning
confidence: 96%
“…Based on the theory of a BWO operating near cutoff [18], the starting current of device operating with a half sinusoidal field profile [appropriate to the field distribution presented in Fig. 7(a)] is (6) where is the number of periods of structure, is the longitudinal electron velocity normalized to the speed of light, is the coupling coefficient introduced in [20], is the linear efficiency given by (7) where The starting current as a function of beam voltage is plotted in Fig. 8 for the parameters corresponding to the parameters of the optimal design.…”
Section: E Starting Current Of a Surface-wave Generatormentioning
confidence: 99%